Impact of livestock production on poverty - evidence from rural Tamil Nadu* - SENTHILKUMAR, G; SELVAKUMAR, K N; PRABU, M; PANDIAN, A SERMASARAVANA; VALLI, C; THILAKAR, P (The Indian Journal of Animal Sciences, 2018)
The present study was undertaken in rural Tamil Nadu to quantify the impact of livestock production on poverty using randomly selected 540 sample respondents. The data were collected through personal interview using pretested interview schedules from sample respondents undergoing various occupations in the six districts covering four agro-climatic zones of Tamil Nadu. The per capita income function of households was fitted to explore the impact of livestock production on poverty. The results implied that the value of assets, education, employment in mandays, livestock occupation had a significant positive impact on the per capita income in contrast to the variables, viz. family size, family dependency ratio and illiteracy, which had negative impact. The per capita income with and without the particular occupation was estimated using the concerned co-efficients. Further, the poverty ratios were worked out in presence of an occupation and in absence of an occupation. The poverty indices were found to be higher for the income with occupation, when compared to the income without occupation for all the chosen occupations, except agricultural labourers. It could be concluded that the presence of agricultural labourer occupation increased the head count ratio (P0) by 0.0370, poverty gap index (P1) by 0.0208, poverty severity index (P2) by 0.0125 and the Watts index (W) by 0.0317. Among all the occupations, the presence of livestock farming decreased the poverty indices by the greatest extent (0.1852 of P0, 0.1002 of P1, 0.0593 of P2, and 0.1562 of W).). Following livestock, fishing had the greater potential of poverty reduction with the reduction values of 0.1852 (P0), 0.0844 (P1), 0.0492 (P2) and 0.1306 (W). Further, it could be revealed that the presence of livestock occupation, decreased the exit time for poverty by 5.22 years and it was 4.35 years for fishing occupation, 3.60 years for non-farm occupation and 2.05 years for cropping activity. Based on the results of the study, it could be concluded that the any poverty alleviation programme should comprise a livestock component.